The hare and the baboon: intersecting violences experienced by African sexual and gender-expansive individuals in the UK asylum system - Chirape, Skye (Department of Psychology, 2025)
Black African sexual and gender-expansive persons seeking asylum in the UK context face specific barriers because of their intersecting identities and experiences related to race, religion, gender, sexuality, cultural background, language, and geographical origin. With idealised white bodies continuously used as the prototype for LGBTQI+ persons seeking asylum, the legislation that protects LGBTQI+ asylum claimants conflicts with the actuality of African sexual and gender-expansive persons' identities and experiences. The research explores co-researchers' narratives about their experiences of the UK asylum regime and how structural and symbolic violences are implicated in the shared narratives. Twenty-seven narratives of the UK asylum system were gathered from diverse sources, including forcibly displaced co-researchers, legal caseworkers, NGO workers and substantive interview documents. The gathered experiences demonstrated structural and symbolic violence perpetrated by the state, through narratives of violent uncertainty, exclusion, vulnerabilisation to exploitation and gendered violence, dislocation and, intersectional discrimination and colonial notions of gender and sexuality. These findings reveal the intersecting and distinct migration obstacles underpinned by anti-Black discrimination that creates systems of racialised and gendered violence against applicants – forming part of the UK's hostile environment and exposing a reality wherein historical legacies of colonialism continue to shape the UK's asylum regime and bordering practices. The findings demonstrate the UK Home Office's significant failings in safeguarding sexual and gender-expansive asylum claimants, and how the COVID-19 pandemic exacerbated their precarious situation. From a decolonial feminist perspective, the participatory action research methodology and principles contribute to knowledge on decolonial and liberatory research practices and offer suggestions for anti-oppressive practices to support just asylum claims.